PERSEPSI DAN EKSPEKTASI KOPERASI TANI SAIYO TERHADAP KONFLIK DENGAN PT. CITRA RIAU SARANA DI DESA PERHENTIAN LUAS KECAMATAN LOGAS TANAH DARAT KABUPATEN KUANTAN SINGINGI - Roby Sahertian; Eri Sayamar; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
Conflict is an unavoidable fact of life and often creative. Conflicts occured when the purpose of society is not the same way. Various of disagreements and conflicts can usually be resolved without violence, and often by results in better situation for most or all of the parties involved. The purpose of this study to know perceptions and expectations of Tani Saiyo Cooperative towards conflict by PT. Citra Riau Sarana in Perhentian Luas District of Logas Tanah Darat Regency of Kuantan Singingi. Determination of the respondents used is key informan. Determination of sample conducted census sampling by thorough sampling techniques. Respondent was taken only 30 members of Tani Saiyo Cooperative as sample. The techniques of data collection used the method of survey. The data has beenob tained qualitative descriptive. The tabulation has done by making distribution of respondents from each of the variables studied. To describe perception variables conflict towards Tani Saiyo cooperative was used 5W+1H. While, expectation variable Scale of Liker's Summated Rating (LSR) was used. The results showed that:(1) Perceptions of Tani Saiyo Cooperative in Perhentian Luas Village has understanding of conflict issue by measured of perception towards of the conflict understanding, perceptions of understanding of the  perpetrators purposes of conflict and perception of conflict perpetrators. (2) Expectations of Tani Saiyo cooperative towards of conflict in the category of high expectations with the score 3,60 as measured from goal, pathway thinking and agency thingking. Keywords: Conflict, Perceptions, and Expecations